2003
DOI: 10.1034/j.1399-3089.2003.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal porcine thymus engraftment, survival and CD4 reconstitution in αGal‐KO mice is impaired in the presence of high levels of antibodies against αGal

Abstract: Xenospecific T-cell tolerance can be induced among murine and human T-cells by porcine thymic grafting. However, anti-alpha 1,3-galactosyltranserase (alphaGal) (Galalpha1-3Galbeta1-4GlcNAc-R) natural antibodies (NAbs) pose a major barrier to porcine xenografts in humans. We used alphaGal knockout (KO) and muchain KO mice to explore the effect of natural anti-alphaGal and other xenoantibodies on porcine thymic engraftment and to examine the potential of thymic tissue to tolerize anti-alphaGal antibody-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…55 In contrast, the induced anti-␣Gal IgM response is largely T-cell dependent. 54,56 Both baseline and induced anti-␣Gal levels were enhanced by nonhematopoietic CR1/CR2 expression, suggesting a role for FDC CR1/CR2 expression in both T-independent and T-dependent Ab responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 In contrast, the induced anti-␣Gal IgM response is largely T-cell dependent. 54,56 Both baseline and induced anti-␣Gal levels were enhanced by nonhematopoietic CR1/CR2 expression, suggesting a role for FDC CR1/CR2 expression in both T-independent and T-dependent Ab responses.…”
Section: Discussionmentioning
confidence: 99%
“…55 In contrast, the induced anti-␣Gal IgM response is largely T-cell dependent. 54,56 Both baseline and induced anti-␣Gal levels were enhanced by nonhematopoietic CR1/CR2 expression, suggesting a role for FDC CR1/CR2 expression in both T-independent and T-dependent Ab responses.Total serum IgM levels were unaffected by the presence or absence of CR1/CR2 on hematopoietic and/or nonhematopoietic cells in our model. Our previous studies showing that anti-␣Gal-and total IgM-producing cells belong to the same B-cell subset 9 led to the expectation that total IgM levels would be reduced in mice lacking nonhematopoietic cell CR1/CR2 expression.…”
mentioning
confidence: 99%
“…avoided with a single treatment by induction of mixed xenogeneic hematopoietic chimerism in a aGalT +/+ rat/ aGalT ÿ/ÿ mouse model using a high dose of bone marrow cells after non-myeloablative conditioning (Kawahara and Sykes, unpublished data) [29,35,37]. The induction of mixed xenogeneic chimerism prevents hyperacute, acute vascular and cell-mediated rejection of primarily vascularized aGal-expressing cardiac xenografts.…”
Section: Rejection Mediated By T Cells B Cells and Nk Cells Can Bementioning
confidence: 99%
“…Thymus xenografts were previously shown to induce and maintain T-dependent but not T-independent B cell unresponsiveness [37]. Another recent study showed that skin xenografts alone induce T cell-independent B cell tolerance but sensitize the Tcell compartment when cotransplanted with thymus tissue with leflunomide treatment [67,68].…”
Section: Xenogeneic Transplantationmentioning
confidence: 99%
“…Unfortunately, clinical xenotransplantation has been thwarted by the vigorous rejection response elicited against solid organs transplanted across a species barrier (2)(3)(4). Transplantation of xenografts between widely disparate species has been limited by rejection due to the presence of natural Abs (5)(6)(7)(8)(9). Even when hyperacute rejection is prevented with plasmapheresis, complement depletion, immunoaffinity columns, or the use of more closely related species, long-term xenotransplantation is still limited by robust acute humoral and cellular immune rejection (10 -16).…”
mentioning
confidence: 99%